A Rare Case of Prostatic Malakoplakia Associated with Prostate Adenocarcinoma: A Case Report and Review of Literature - Orlando Tuy Rances; Jeffrey Santos So (Interna Publishing, 2023)
Malakoplakia is a chronic granulomatous condition that has been rarely seen affecting the prostate. Isolated malakoplakia of the prostate occurring together with prostatic adenocarcinoma is rarer still with only 9 previously recorded cases. We present a case diagnosed through needle biopsy with prostatic adenocarcinoma and then on subsequent prostatectomy was diagnosed with extensive malakoplakia occurring with the carcinoma. Patient was noted to have a urinary tract infection (UTI) 2 weeks after needle biopsy and notably, 4 of the 9 previously reported cases also presented with UTI following their biopsies. The theory that prostatic malakoplakia may be a complication of the prostate needle biopsy is logically possible, but due to the paucity in cases, it is difficult to infer causality.